Enhancing Underwater Audio Transmission with Secure Li-Fi Technology (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Ensuring the security of audio transmission becomes crucial as underwater communication systems become more and more important in a variety of areas, including defense, marine research, and offshore organizations. For this reason, Li-Fi technology is an innovative solution that uses its immunity to electromagnetic interference to get around the restrictions of conventional radio frequencies. Li-Fi allows for high-speed data transfer while reducing interference and signal degradation by encoding audio onto light waves. It highlights the benefits of Li-Fi over RF techniques for underwater communication and investigates how encryption algorithms might be integrated to improve data security. The article discusses the difficulties associated with underwater communication, such as signal attenuation and monitoring susceptibility, and it offers a thorough solution that combines authentication procedures and encryption techniques to guarantee the integrity and confidentiality of audio data. To improve the dependability of communication systems in difficult aquatic situations, this research presents new approaches to the essential demand for secure audio transmission in underwater environments.